Protein mimetic amyloid inhibitor potently abrogates cancer-associated mutant p53 aggregation and restores tumor suppressor function - L. Palanikumar (Nature Portfolio, 2021)
Amyloid aggregation of mutant p53 contributes to its loss of tumor suppressor function and oncogenic gain-of-function. Here, the authors use a protein mimetic to abrogate mutant p53 aggregation and rescue p53 function, which inhibits cancer cell proliferation in vitro and halts tumor growth in vivo.